MANAJEMEN PERTUNJUKAN KOMPOSISI MUSIK LAGU TALEMPONG RATOK TIRAMA: SUATU PENDEKATAN WORD MUSIK - Ryvaldo Apriandi; Ediwar Ediwar; Syahri Anton (Bajang Institute, 2023)
Talempong uwaik is talempong that played by older women in area of Agam that developed at Nagari Paninjauan Maninjau, Tanjung Raya regency. The term Talempong uwaik-uwaik is composed of female, while the term of uwaik itself is derived from the reference to the old women. Talempong uwai-uwaik notes include one of ratok tirama song, based on the production of talempong uwaik-uwaik ratok tirama song, the production found short recurring pattern of melody. Artist of tradision called this musical phenomenon baulang (repetitious). Saik Ratok Tirama creation is also used by the World Music approach with guitar instruments, bass, flutes, conga, talempong, keyboard, and drums. The production divides the work into two parts. In the first part, it is focused on the form of the razing ratok tirama tradition song by using traditional instruments of the song itself, such as talempong, gandang, aguang, gadabiak, the glass bottle, and giriang-giriang. In the second part, the creation focused on the short-repeated melodic pattern.